Minimal Pairs: An Analysis Of College Students' English Pronunciation Errors - Khairunnisa Khairunnisa; Kezia Nur Elizanti Purba; Yani Lubis (Universitas Dehasen Bengkulu, 2023)
This study aims to analyze pronunciation in English by using minimal pairs. A qualitative research method with a quantitative approach was used with the number of participants 15 students majoring in English education, North Sumatra State Islamic University. In collecting data, pronounciation tests and listening tests were analyzed using descriptive qualitative techniques. The minimum pairs tested were: /k/ - /g/, /p/ - /b/, /t/ - /Î¸/, /p/ - /f/, /s/ - /Êƒ/, /s/ - /z/, /tÊƒ/ - /dÊ’/, /f/ - /v/, /t/ - /d/. The highest number of errors in the pronounciation test reached 66.7% and in the listening test reached 73.3%. More knowledge about phonology is still needed so that pronounciation skills are even better. If pronounciation is good, listening skills will also be good and communication in English can run smoothly without any misunderstanding.